2020
DOI: 10.1007/s00590-020-02751-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and re-operation rates in one thousand and three hundred tibial fractures from the Swedish Fracture Register

Abstract: Purpose Approximately, 50 persons per 100,000 per year sustain a tibial fracture. There is, however, a lack of large cohort studies that describe the treatment and re-operation frequencies of tibial fractures. The aim of this study was to describe the treatment and re-operation rates of tibial fractures in all segments of the tibia. Methods Data related to all patients aged 16 and above treated for tibial fractures (ICD-10 S82.10-31) at Sahlgrenska University Hospital i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…This assumption is supported by the higher rate of patient-requested reoperations we found in patients ≤ 59 years old. Similar findings have been demonstrated for other surgically treated fractures (Wennergren et al 2021 ). Elderly patients are generally reluctant to undergo additional surgery and probably more inclined to accept dysfunction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This assumption is supported by the higher rate of patient-requested reoperations we found in patients ≤ 59 years old. Similar findings have been demonstrated for other surgically treated fractures (Wennergren et al 2021 ). Elderly patients are generally reluctant to undergo additional surgery and probably more inclined to accept dysfunction.…”
Section: Discussionsupporting
confidence: 90%
“…High validity for reoperations is a proven difficulty in register-based studies and underreporting leads to an underestimation of the risk of reoperation (Wennergren et al 2021 ). To avoid reoperations not registered in the SFR remaining undetected, only patients primarily treated and eligible for follow-up at SUH were included.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of operative with nonoperative treatment showed that the risk of TKRS increased in the operative group during the first 2 years and thereafter remained about double. Multi-fragmentary fractures have previously been reported as risk factors for reoperations after TPF ( 16 ). In our study, it is likely that the patients in the operative group sustained more displaced and more multi-fragmentary fractures than the patients in the nonoperative treatment group due to high-energy trauma in the younger patients or poor (osteoporotic) bone quality in the older patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, the reoperation rate is dependent on accurate registrations of performed re-operations. This process, with its strengths and limitations, has been validated in defined cohorts [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The next reasonable step was to conduct descriptive studies of the epidemiology, incidence and mortality of different fractures [ 22 26 , 36 – 40 ]. Studies designed to evaluate outcome after the treatment of fractures have been conducted and many are ongoing [ 8 , 9 , 41 , 42 ]. Most publications have focused on the validation of essential features in the SFR or have been descriptive, basic epidemiological studies, as was the intention described above.…”
Section: Introductionmentioning
confidence: 99%